Informal agricultural trade and trans-border farmers between Malaysia and Indonesia - Fariastuti, Djafar; Mohd Khairul Hisyam, Hassan; Dzul Hadzwan, Husaini (College of Business, Tennessee State University, 2016)
Agricultural products are important commodities in the informal trade between countries in developing areas. However, previous studies on this issue tended to concentrate on countries in Africa and trade through official border posts. For years, Indonesian farmers have been selling vegetables to Malaysia via unofficial border posts. The Indonesians tend to view selling products in Malaysia as profitable because of the higher price of the product compared to that in Indonesia. The picture is not entirely true since the farmers are only price takers. Three objectives are proposed in this study. The first objective is to explore the supply, demand and price of vegetables in Cross-Border Informal Trade (CBIT), followed by an estimate of the value of CBIT as the second objective. The last objective is to examine the effect on the vegetable supply of price, number of days trading across the border and the experience as a cross-border trader. The study was conducted at Serikin village, Bau District, Sarawak Malaysia, which shares a common border with Jagoi village, Bengkayang district, West Kalimantan Indonesia. The primary data were obtained by survey using a structured questionnaire while qualitative data were gathered through in-depth interviews and observation. A total of 62 trans-border farmers were successfully interviewed using a structured questionnaire. The first and second objectives are answered by exploring data obtained from the structured questionnaires, in-depth interviews and observation. The third objective is met based on data obtained through a structured questionnaire, which was analyzed by employing multiple regression. The study shows the weak bargaining position of the Indonesian trans-border farmers in Sarawak and an oversupply of vegetables depressing the price of the vegetables. At least 30 types of vegetable are imported informally from West Kalimantan to Sarawak, weighing a total of 18 ton, and with a total value of MYR 42,000 per day. The number of day trades across the border per week influences the vegetable supply positively and significantly. Close location, lack of accessibility to the domestic market and high profit seem to be the most important factors in motivating the Indonesian farmers to trade informally in Sarawak, rather than the price of the vegetables and experience as cross-border informal traders. The Indonesian authorities may reduce the vegetable supply to Sarawak by extending the internal market and developing an agro-tourism industry in West Kalimantan. The Malaysian and Indonesian authorities may formalize the status of the Jagoi-Serikin border post enabling them to monitor the cross-border trade between the two countries.